Negative Effects of a Multimodal Inpatient CBASP Program: Rate of Occurrence and Their Impact on Treatment Outcome in Chronic and Treatment-Resistant Depression - Herzog, Philipp; Häusler, Sophia; Normann, Claus; Brakemeier, Eva-Lotta (Frontiers in Psychiatry, 2021)
Background: A growing number of studies indicate that the Cognitive Behavioral Analysis System of Psychotherapy (CBASP) is effective in treating chronic depression. However, there is no systematic research into possible negative effects. Therefore, the objectives of the study were to investigate the frequency of negative effects of an inpatient CBASP program and their impact on treatment response. Methods: 52 patients with chronic depression and treatment-resistance who completed the structured 12-weeks inpatient CBASP program in an open trial retrospectively completed the Inventory for the Assessment of Negative Effects of Psychotherapy during follow-up data-collection. Severity of depressive symptoms was assessed self- and observer-rated at admission, discharge and 6-months follow-up. Frequencies of negative effects were calculated and binary logistic regression analyses were conducted to determine the relationship to treatment outcome. Results: 92.3% of patients reported having experienced at least one negative effect and 45.2% indicated dependence on their therapist. Stigmatization and financial concerns as well as intrapersonal changes were reported by about one third. Only dependence on the therapist negatively impacted treatment outcome in both outcome measures. Conclusions: Most of the reported negative effects appear to be benign. However, since dependence on the therapist seems to have a negative impact on treatment outcome, therapists should consciously address this during therapy.